2020
DOI: 10.1177/1120672120963450
|View full text |Cite
|
Sign up to set email alerts
|

Dense laser at the papillomacular bundle does not cause loss of visual function

Abstract: Introduction: Juxtapapillary laser (JPL) photocoagulation in the region of the papillomacular bundle, temporal to the optic nerve, has become routine care in disorders such as optic disc pit maculopathy. Despite evidence demonstrating safe and effective use of this approach, there is still a lack of consensus in the literature, due to the perceived risk of loss of visual function. Instances of such misplaced caution could result in inadequate treatment protocols. Methods: An observational series of five cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Thus, it should not affect the most superficial layers of the retina and the RNFL. However, there are conflicting evidence on potential damages to the papillomacular bundle, some authors considering them unlikely [31], while others have reported significant visual field defect [32]. In all cases, laser should be performed cautiously, using the lowest energy as possible.…”
Section: Therapeutic Managementmentioning
confidence: 99%
“…Thus, it should not affect the most superficial layers of the retina and the RNFL. However, there are conflicting evidence on potential damages to the papillomacular bundle, some authors considering them unlikely [31], while others have reported significant visual field defect [32]. In all cases, laser should be performed cautiously, using the lowest energy as possible.…”
Section: Therapeutic Managementmentioning
confidence: 99%